2013
DOI: 10.1021/jp311789f
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Landscape, Photochemistry, and Infrared Spectra of Sulfanilamide

Abstract: A combined matrix isolation FTIR and theoretical DFT(B3LYP)/6-311++G(3df,3pd) study of sulfanilamide (SA) was performed. The full conformational search on the potential energy surface of the compound allowed the identification of four different minima, all of them bearing the sulfamide nitrogen atom placed in the perpendicular orientation relatively to the aromatic ring and differing from each other in the orientation of the hydrogen atoms connected to the two nitrogen atoms of the molecule. All conformers wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 61 publications
2
16
0
Order By: Relevance
“…On the other hand, preliminary calculations performed with the smaller 6–311++G(d,p) basis set were found to strongly underestimate the frequencies for the modes localized in the ‐SO 2 ‐ fragment, in particular the two stretching vibrations and the scissoring and wagging modes. These results follow the trends described in previous studies in which the infrared spectra of other molecules bearing the ‐SO 2 ‐ moiety were discussed. It has been shown that the use of highly polarized basis sets is necessary to provide the wavefunction the required flexibility to account properly for properties (including vibrational frequencies) of hypervalent sulphur containing molecules.…”
Section: Resultssupporting
confidence: 91%
“…On the other hand, preliminary calculations performed with the smaller 6–311++G(d,p) basis set were found to strongly underestimate the frequencies for the modes localized in the ‐SO 2 ‐ fragment, in particular the two stretching vibrations and the scissoring and wagging modes. These results follow the trends described in previous studies in which the infrared spectra of other molecules bearing the ‐SO 2 ‐ moiety were discussed. It has been shown that the use of highly polarized basis sets is necessary to provide the wavefunction the required flexibility to account properly for properties (including vibrational frequencies) of hypervalent sulphur containing molecules.…”
Section: Resultssupporting
confidence: 91%
“…Importantly, if we consider the position of the sulphur bound oxygen atoms with respect to the piperazine nitrogen substituents, family I and IV present the anti and the fully eclipsed conformations, respectively ( Figure 3B). Thus, in agreement with previously reported results on benzosulfonamide derivatives [35][36][37] the two most favoured families of conformers are I and IV, with family I (i.e., anti conformation of the oxygen atoms with respect to the piperazine nitrogen substituents) representing the GM family, as found in the crystal structure of N,N-dimethyltoluene-p-sulfonamide [38].…”
Section: Computational Studies and Sar Analysissupporting
confidence: 92%
“…Originally, protonation and deprotonation sites in sulfanilamide were derived from UV spectra under acidic and basic conditions, as well as from an analysis of the possible resonance 0123456789(). : V,-vol structures and their influence on frequency and integrated absorbance of the UV bands [20][21][22]. Later also pH-dependent Raman spectra were reported [23].…”
Section: Introductionmentioning
confidence: 99%